Elastic local buckling of periodic sinusoidal corrugated composite panels subjected to in-plane shear - Pathirana, Sachinthani; Qiao, Pizhong (Thin-walled structures, 2020)
The critical local buckling instability of simply supported sinusoidal panels subjected to in-plane shear loading is investigated semi-analytically using the Rayleigh-Ritz method. Due to significant weight-strength saving and increased out-of-plane rigidity, these thin corrugated structural elements have gained wide recognition as an alternative to flat plate structural elements. To utilize these structures effectively in applications, such as civil infrastructure, aircraft wings, among many others, it is important to attain a comprehensive understanding of the failure mechanisms of these structures. Such corrugated panels are easily analyzed by modeling as an equivalent flat plate; however, this approximate method cannot capture the local buckling effect due to the complicated geometries of sinusoidal panels. Hence, a more precise solution is developed to accurately predict the local buckling behavior based on classical shell theory using a representative periodic structural element which encapsulates the periodic buckling nature of the panel in shear. Excellent correlation is observed with the results based on the numerical finite element analysis. Parametric studies are conducted to explore the effects of the thickness, aspect ratio, corrugated amplitude and material properties of the panel on buckling. The derived semi-analytical solution can accurately capture the local buckling behavior at any thickness, any aspect ratios, and high corrugated amplitudes within the range of thin-walled shells. The proposed semi-analytical solution can be confidently used to aid in efficient and accurate design analysis and optimization of corrugated panels. •Semi-analytical solution for local buckling of sinusoidal panels under in-plane shear is obtained using Rayleigh-Ritz method.•Good agreement between the semi-analytical solution and FE prediction of a period sinusoidal-corrugated cell is reached.•Shear local buckling capacity is primarily governed by the curvature variation in regions of minimum curvatures.